Finances of the Workers´ Insurance Fund, 1925-1952 - Ahumada Benítez, Daniel (Universidad Academia de Humanismo Cristiano, 2023)
The purpose of this article is to analyze the financial evolution of the Caja de Seguro Obrero Obligatorio (CSO) [Workers’ Insurance Fund] throughout 1925 and 1952. The main findings are that: 1) the Workers’ Insurance Fund never had a deficit year, despite experiencing significant financial difficulties; 2) spending on health benefits was always much higher than spending on other benefits such as pensions; and 3) employer contributions were always the first source of income. This work also contributes to the construction of the first series with the finances of the main social welfare institution between 1925 and 1980.